Incidence of Antibiotic Resistant Escherichia Coli In UTI Suspected Patients-A Single Centered Study - Chakraborty, SR; Shuvo, MGS (Stamford Journal of Microbiology, 2023)
The evaluation of antimicrobial sensitivity patterns has a significant role in prescribing antimicrobial drugs to treat patients suffering from urinary tract infections (UTIs). This study assessed the etiology and antimicrobial susceptibility of the common uropathogens as those were detected in Dhaka, Bangladesh. This study was conducted following the culture and identification of pathogenic microorganisms from patients of all age groups and sexes. A total of 110 urine samples were collected from suspected UTI patients for culture and sensitivity as advised by the physicians. Female patients (76.4%) were dominant over male patients (23.6%) and patients were 0 to 90 years of age. From these samples, 25 Escherichia coli were isolated from culture-positive cases to determine antibiotic sensitivity patterns. Most of these isolates were resistant to Azithromycin (100%), Nalidixic Acid (80%), Cotrimoxazole (54%), Ciprofloxacin (44%) and Cefixime (44%). The present study emphasized the necessity of standard microbiological screening techniques to evaluate the etiological characteristics required to effectively treat UTI patients. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 21-24